The Use of Taboo Words in Denpasar - Mahayana, I Made Astu; Suarjaya, Anak Agung Gede; Putri, Dewa Ayu Dyah Pertiwi (International Journal of Psychosocial Rehabilitation, 2020)
Taboo words are considered to be inappropriate to use in every language in the world, especially Denpasar. This research aimed to analyze the motives, forms, and types of taboo words found in daily conversation used by people in Denpasar. This research is descriptive qualitative study. The observation method was used in collecting the data. After observing the data, the recording method and note taking technique were also used to collect the data. Based on the results, it was found that (1) the motives of taboo words used by the people are psychological, social, and linguistic motives. Psychologically, the taboo words are used for (a) expressing anger, (b) expressing astonishment, (c) expressing disappointment, and (d) expressing happiness. Furthermore, they are socially used for (e) attracting people’s attention, (f) insulting someone, (g) showing intimacy or solidarity, (h) showing contempt, (i) showing sympathy, and (j) amusing someone. And linguistically, they are used for (k) giving emphasis on what they try to communicate. (2) Based on the form, they grammatically consist of word, phrase, compound, and reduplication. Finally, the kinds of taboo words found in this research were: (a) abusive swearing/epithets), (b) obscenity, (c) cursing, (d) religious matters/profanity/blasphemy, (e) names of one’s in-laws, (f) animal imagery, (g) Children’s insults (abnormal physical, psychological, or social characteristics), (h) social deviations, (i) ethnic and racial slurs, (j) vulgarity, and (k) slang.